Matching networks to needs : travel needs and the configuration and management of local movement networks in South African cities - Behrens, Roger (School of Architecture, Planning and Geomatics, 2019)
Motivated by disquiet that walking, as both a travel mode and as a segment of public transport trips, is not accommodated well in South African cities, this dissertation has two central aims. The first is to understand better the need for travel by non-motorised modes and within local areas. The second is to contribute to the improvement of local area movement network configuration and management practices. The research is primarily exploratory in nature and was conducted within a 'critical social science' paradigm-in which the research process was driven by a series of questions regarding the critical interrogation of these practices. It explores some of the implications for practice of a post-apartheid urban transport policy discourse that prioritises understanding travel need, managing road space, and accommodating public transport users and pedestrians. Reviews of literature, examination of codes of practice, and interviews with practitioners were conducted to trace the origins and nature of practices in the fields of travel analysis and local network planning and to investigate evidence of relationships between local network planning practices and improved local travel conditions. A household travel survey was administered in metropolitan Cape Town to gather data on travel behaviour across various income bands and in different residential locations. The survey employed an innovative activity-based method, with theoretical origins in time geography. With the use of computer-assisted personal interviewing technology, it involved members of 204 households recording their activity schedule over a 24-hour period. The data were analysed using conventional methods of filtered cross-tabulation, as well as time-space instruments. The research found, inter alia, that as a result of being routinely excluded or underestimated in past surveys, the importance of walking has not been fully understood. Walking would appear to be particularly important in satisfying the travel needs of middle-and low-income households, and walking distance findings would appear to refute assumptions regarding the introverted nature of pedestrian trips that underlie conventional local network configuration practices. In the light of these and other findings the dissertation argues for functionally 'fuzzy' local networks within which pedestrians and cyclists are accommodated on 'permeable' networks of footways, pathways, cycleways and shared roadways, while motor cars are accommodated on variously discontinuous roadway networks. The dissertation also argues for the strategic identification of local areas requiring priority attention, and the preparation of integrated local area plans incorporating co-ordinated and proactive pedestrian planning, bicycle planning and traffic calming.